HUBUNGAN ANTARA KECERDASAN EMOSI DENGAN KINERJA PUSTAKAWAN DI PERPUSTAKAAN - Farhanah, Nazzatul; Zulaikha, Sri Rohyanti (Universitas Padjadjaran, 2016)
The purposes of this research are: 1) To understand the level of librarianâs emotional intelligence at Perpustakaan Kota Yogyakarta, 2) To understand the level of librarianâs performance at Perpustakaan Kota Yogyakarta, 3) To understand the correlation between the librarianâs emotional intelligence and the librarianâs performance at Perpustakaan Kota Yogyakarta. The type of this research is a quantitative research. The population of this research are all the librarians at Perpustakaan Kota Yogyakarta which are counted 26 librarians. To collect the research data, the researcher uses: questionnaire, observation, interview, and documentation. The measurement of the data uses likert scale with 4 alternative answers. There are three steps of data analysis, they are: descriptive analysis uses mean and grand mean, correlation test uses pearsonâs product moment, and hypothesis test by compare the score of r measurement and r table. The results of this research are: 1) The level of librarianâs emotional intelligence is good; 2) The level of librarianâs performance is good; 3) There is a positive correlation between the librarianâs emotional intelligence and the librarianâs performance, it is known by the score of r which is positive, this score also shows that there is a strong correlation between the two variables. Some indicators need to be increase because the score is lower than the average. The librarians ask to the institution to give more chance and space for share their ideas related with their tasks and their responsibility. The librarians also complained about the high of work stress, that make the difficulties of self managing.Penelitian ini bertujuan untuk 1) Mengetahui tingkat kecerdasan emosi pustakawan di Perpustakaan Kota Yogyakarta, 2) Mengetahui tingkat kinerja pustakawan di Perpustakaan Kota Yogyakarta, 3) Mengetahui hubungan antara kecerdasan emosi dan kinerja pustakawan di Perpustakaan Kota Yogyakarta. Penelitian ini merupakan penelitian deskriptif kuantitatif. Populasinya adalah seluruh pustakawan di Perpustakaan Kota Yogyakarta yang berjumlah 26 orang. Metode pengumpulan data menggunakan kuisioner, observasi, wawancara, dan dokumentasi. Pengukuran data menggunakan skala likert dengan rentang skala 4 alternatif jawaban. Terdapat tiga tahap analisis data, yaitu analisis data deskriptif menggunakan mean dan grand mean, uji korelasi menggunakan rumus pearsonâs product moment dan uji hipotesis dengan membandingkan antara r hitung dengan r tabel. Hasil penelitian menunjukkan bahwa 1) kecerdasan emosi pustakawan di Perpustakaan Kota Yogyakarta dalam tingkat baik. 2) Kinerja pustakawan di Perpustakaan Kota Yogyakarta berada pada tingkat baik. 3) Terdapat hubungan yang positif antara kecerdasan emosi dengan kinerja pustakawan di Perpustakaan Kota Yogyakarta di buktikan dengan nilai r hitung yang menunjukkan bahwa tingkat hubungan antara dua variabel sangat kuat. Beberapa indikator perlu ditingkatkan karena mendapatkan skor dibawah rata-rata. Pustakawan berharap agar institusinya memberikan kesempatan dan ruang yang lebih bagi pustakawan untuk menyampaikan gagasan yang berkaitan dengan tugas dan fungsinya. Serta beban kerja yang cukup tinggi membuat pustakawan menjadi kesulitan untuk melakukan pengelolaan diri dengan baik.